Analisis Penggunakan E-Wallet Dalam Bertransaksi Keuangan Mahasiswa Universitas Sultan Maulana Hasanuddin Banten - Qurtubi El-haqnur; Tiara Citra Yuliani; Dewi Hartaty; Budi Sudrajat; Henny Saraswati; Wahyu Hidayat (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
Internet users are growing rapidly from time to time all over the world, including Indonesia. As a result, their consumer's need for making payments has changed to non-cash payments, namely electronic wallets, which are becoming a huge potential in their e-commerce market. Their preference for e-wallet transactions increases compared to using cash. Most of its users are millennials, including students. This study has knowledge relevant to the use of e-wallets and the reasons behind their use. Their study involved college students, which consisted of nine female students, and one male student whose ages varied between 19 and 23 years. This study uses a quantitative method with an in-depth approach as a technique for collecting primary data and secondary data obtained from related websites. The results of this study yielded the following data: 1. Student knowledge about e-wallets has a positive and significant impact on student transaction interest based on the results, the t count is 10,160, which is greater than the t table, which is 1,989. 2. From the results of the deitemination coefficient test, it can be seen that the variable effect of student knowledge about e-wallets on interest in financial transactions is as much as 52.3%. This can be seen from the R value of squiarei in the variable knowledge of students about Islamic banks, which is equal to 0.523. The remaining 47.7% is affected by variables that are not included in the research being studied. On the other hand, e-wallets are not only understood as a place to store money electronically, but also as digital payments such as OVO, Gopay and DANA. and students not only feel comfortable, but also make payments easier because they can be done anywhere as long as the user is connected to the internet.